Architecture and performance of multi-hop wireless ad-hoc routing protocol (MultiWARP) - Van Der Werf, Steven Martĳn (Curtin University, 2010)
In recent years, a great deal of attention has been given to wireless connectivity solutions that are capable of establishing wireless ad-hoc networks between mobile nodes. Whilst most of these networks are formed using a combination of fixed and mobile infrastructure, completely infrastructure-less networks are thought to become more commonplace in the future. Moreover, this type of network structure seeks to utilise multi-hop connectivity between mobile nodes rather than the traditional single-hop connectivity established between fixed access points.The initial configuration phase and subsequent maintenance phase of a multi-hop wireless ad-hoc network requires the use of appropriate routing functions to exist between the mobile nodes. Therefore, it is essential that a routing protocol capable of determining correct and optimal routing path information in the presence of node mobility and the mobile radio environment be sought. Furthermore, it is beneficial to utilise the limited wireless bandwidth efficiently, such that a routing protocol should be designed specifically in the context of a multi-hop wireless ad-hoc network topology. This can be achieved through employing a non-hierarchical approach and using neighbouring nodes to act as intermediate relay nodes.The proposed routing protocol, called the Multi-hop Wireless Ad-hoc Routing Protocol (MultiWARP), is comprised of both a proactive and reactive routing component, thus forming a hybrid protocol which is able to exploit the benefits of each component. It is shown that manipulating these two components within the context of an awareness region, which divides the network into 2 regions, the routing overhead can be minimised. For the proactive component, the necessary network topology information that must be transmitted between neighbouring nodes is encoded within a routing update (RUPDT) packet. In this study, three alternative RUPDT encoding schemes have been formulated to encode the network topology in an efficient manner to reduce the RUPDT packet size.For the reactive component, a novel covercasting mechanism is designed that minimises the number of route request (RREQ) transmissions required to determine the routing path by utilising existing routing table information. Supplementary techniques are then utilised, such as snooping, route repair, and route optimisation to further optimise performance and minimise the route discovery delay (latency). This same covercasting mechanism is then utilised to efficiently transmit periodic RUPDT packets between neighbouring nodes to maintain routing table validity at each node, without having to resort to flooding which causes the “broadcast storm problem”. In addition, several route selection algorithms are considered which distribute traffic data between the intermediate relay nodes comprising the ad-hoc network.The performance and computational complexity of the proposed hybrid routing protocol is shown by means of computer simulations and theoretical analysis. Various traffic scenarios and topologies are presented to obtain the routing protocol performance metric results, and these are compared with other protocols found in the literature. For a multi-hop wireless ad-hoc network, it is shown that the proposed hybrid routing protocol, MultiWARP, is able to achieve higher average system performance in terms of improved throughput and stability performance when compared to other wireless ad-hoc routing protocols, such as DSR.